Subclinical social anxiety in healthy young adults: Cortisol and subjective anxiety in response to acute stress - Mirete, Marcos; Molina, Sergio; Villada, Carolina; Hidalgo, Vanesa; Salvador, Alicia (Anales de Psicología / Annals of Psychology, 2021)
There is no consensus about the pattern of cortisol release and its relationship with subjective anxiety in situations of stress in the population with social anxiety. Our aim was to determine the cortisol and subjective anxiety response in individuals with social anxiety subjected to an acute psychosocial stressor. 26 college students (58.6% males), mean age = 21.62 ± 0.43, were exposed to the stress or control adaptation of the Maastricht Acute Stress Test. Salivary cortisol and subjective anxiety were measured before, during, and after stress. Participants showed an increase in cortisol levels during the stress and post-stress phases, with a significantly higher response in those with high social anxiety. Participants with high social anxiety also showed, as a tendency, higher levels of subjective anxiety, especially in the post-stress phase. Only in the stress phase, cortisol and subjective anxiety correlated significantly in socially anxious participants. The findings support a cortisol hyperresponsiveness in a young, non-clinical population with high social anxiety. Future research should focus on the factors involved and the effects of this physiological response on health. Furthermore, the need to control social anxiety in experiments using a laboratory psychosocial stressor is highlighted.